PREVALENCE AND FACTORS ASSOCIATED WITH UNSUPPRESSED VIRAL LOADS AMONG ADOLESCENTS ON ART ATTENDING ART CLINIC AT BUSEMBATIA HEALTH CENTER III, BUGWERI DISTRICT, UGANDA. A CROSS-SECTIONAL STUDY. - Gubira, Christopher; Ssemuweba, Frank (Student's Journal of Health Research Africa, 2025)
Background Adolescents living with HIV are put on ART to improve their quality of life. The emerging failure to have their viral load suppressed is increasing. However, risk factors for failure of viral load suppression in a rural ART clinic are not well documented. This study sought to find out the prevalence and factors associated with unsuppressed viral loads among HIV/AIDS-positive adolescents in the ART clinic of Busembatia Health Centre III. Methodology. A descriptive cross-sectional study was used for HIV positive adolescents attending ART Clinic at Busembatia Health Centre III, Bugweri District. A Kish and Leslie statistical formula was used to obtain the sample size and a random sampling technique was used among 92 adolescents. Data about the adolescents was both extracted from the Client forms and also obtained through questionnaires. Results. 51(55.44%) of the participants were female,50(54.35%) of the adolescents were aged 12-13 years and the majority of them were single 89(96.74%). 21% of the participants had unsuppressed viral loads. The established patient-related factors were; Substance abuse 16(84.21%), Sexual behaviors 10(52.63%), Knowledge about HIV 16(84.21%) and clinical-related factors were poor adherence 4(21.05%), Multimorbidity and opportunistic infections 6(31.58%), poor nutritional status 6(31.58%), 12(63.15%) were in WHO clinical stage and 4 (21.05%) of the unsuppressed adolescent had their regimen changed. Conclusion. Prevalence of unsuppressed viral loads was high and the factors associated with viral load unsuppression are numerous, unique and thus require unique interventions. Recommendation. The ART clinic personnel and Implementing partners should engage the adolescents on ART, parents/guardians, and teachers in identifying their problems and the challenges and try to find and or address these problems.